2017
DOI: 10.1088/1757-899x/275/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

The Research Progress of Zr Based Amorphous Composite Materials

Abstract: Based on the introduction and forms of the second phase the Zr based amorphous composites was classified.This paper introduced the research work of the endogenous phase-Zr based amorphous composite materials, the particles-Zr based amorphous composites, fiber-Zr based amorphous composite materials, the skeleton-Zr based amorphous composite materials, and prospected the development prospect of Zr based amorphous composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Ceramic polymer material is a functional composite material that has developed rapidly in recent years. 1 It consists of polymer and inorganic filler. This material has the plasticity and mechanical properties at room temperature like regular plastic and rubber.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ceramic polymer material is a functional composite material that has developed rapidly in recent years. 1 It consists of polymer and inorganic filler. This material has the plasticity and mechanical properties at room temperature like regular plastic and rubber.…”
Section: Introductionmentioning
confidence: 99%
“…This ceramic shell prevents the heat/ oxygen transferring, thereby protecting the internal wires and gaining time for rescuing people and property from a fire. 1,2 The ceramic materials sintered at high temperature are mostly prepared by precursor of silicon-containing chemical substance [11][12][13] and silicone rubber. [14][15][16] Silicone rubber contains silicon and oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, extrinsic crystalline phases such as TiC, TiB, WC, ZrC or ZrO 2 , dendrites (a tree-like crystalline structure) and crystalline phases that undergo the diffusionless phase transformation during plastic deformation can improve ductility to more than 5%. [15][16][17][18] It has been reported that the improved ductility in the extrinsic phase and dendrite-reinforced MGs associates with work-softening, whereas a diffusionless phase transformation during plastic deformation can significantly enhance the ductility of MGs accompanied with obvious work-hardening. [19][20][21] Up to now, the discovered parent phase with diffusionless transformation in the MG matrix is only the equiatomic CuZr intermetallic compound with a body-centered-cubic (bcc) structure (B2 phase).…”
Section: Introductionmentioning
confidence: 99%